Job satisfaction mediates the effect of self-efficacy on work engagement among physical education teachers in economically disadvantaged areas - Hongping Zhou; Shi Qi Xu; Dong-Hwa Chung; De Xin Dang (PLoS ONE, 2025)
The unequal distribution of educational resources across regions with varying levels of socioeconomic development remains a global issue. Teachers in economically disadvantaged areas often exhibit lower levels of work engagement due to constraints in resources and limited opportunities for professional growth. This issue is particularly pronounced among physical education (PE) teachers, as PE is frequently regarded as a marginal subject. As a result, PE teachers receive less recognition from administrators and parents, encounter greater professional challenges, and experience diminished work engagement. Enhancing self-efficacy and job satisfaction has been identified as a critical strategy for improving work engagement. However, these relationships among PE teachers in underdeveloped regions remain insufficiently explored. To address this gap, this survey collected 472 questionnaire responses from rural primary school teachers, using a 5-point Likert scale survey. A path analysis model was employed to examine the direct and indirect effects of self-efficacy and job satisfaction on work engagement. The findings reveal that self-efficacy exerts an indirect influence on work engagement, with job satisfaction serving as a key mediating factor. These results suggest that fostering self-efficacy among PE teachers in economically disadvantaged areas can enhance job satisfaction, thereby leading to increased work engagement.